Holistic Learning Versus Instrumentalism in Teacher Education: Lessons from Values Pedagogy and Related Research - Terence Lovat (MDPI AG, 2020)
This article constitutes a literature review, focusing on the idea of holistic learning, as found in key sources, and its essential contrasting with instrumentalist approaches to learning. It will move to explore updated research on holistic learning factors, with special attention to insights gleaned from values pedagogy and the research that underpins it. The article will juxtapose those insights with the instrumentalism that, it will allege, too often dictates teacher education directions. The article will conclude with an argument that teacher education has become, in modern times, a service industry, too often serving the agendas of governments and teacher unions, rather than preparing teachers to follow the guidelines provided by the latest research into student wellbeing and societal betterment. The article will focus especially on a number of Australian examples to mount the argument that nonetheless applies more generally across Western domains.